Maximal exercise testing in patients with spontaneous angina pectoris associated with transiet ST segment elevation. Risks and electrocardiographic findings. - Detry, J M (1975)
Six patients with spontaneous angina associated with transient ST segment elevation had a multistate maximal exercise (bicycle) test. In 5 patients, typical electrocardiographic changes were recorded during exercise, namely ST segment elevation often accompanied by an increase in the voltage of the R wave and a widening of the QRS complex. Four of these patients developed severe rhythm disturbances: ventricular tachycardia (2 cases) and ventricular flutter (1 case) were the reason for early interruption of the test in 3 patients, while 1 patient had a short run of ventricular tachycardia after exercise. These rhythm disturbances which spontaneously regressed in all cases were consistently preceded by obvious ST elevation and in 2 patients were attended by slight chest discomfort. Maximal exercise testing of patients suspected of variant angina provides important diagnostic information in many patients, but the risks of potentially lethal arrhythmias should be considered and resuscitation facilities should always be immediately available.